Psychological Support and Psychotherapy during the COVID-19 Outbreak: First Response of Practitioners - Velykodna, Mariana; Frankova, Iryna (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Providers of psychological support and psychotherapy during the COVID-19 pandemic unfolding were facing the new unavoidable reality, which required making urgent changes in their practice. The paper aimed to study the "first responses” of psychologists and psychotherapists to the COVID-19 pandemic situation with its uncertainty before the lockdown. An online survey was developed and distributed among psychologists and psychotherapists from Ukraine from 14 to March 16, 2020. Results showed that among survey respondents (n=145), 35.9% had already changed their practice somehow, and 75.2% had been considering how their practice might be modified. The more often the COVID-19 pandemic was discussed by patients, the more often it affected the style and technique of the corresponding specialists, thereby pushing psychotherapists to change the format of their work. Practice restrictions due to quarantine measures affected more affiliated consultants, while difficulties with setting (e.g., canceled sessions, financial issues) were more frequent among private practice consultants, and both proposed online consultations to their patients. In conclusion, the pandemic situation caused relevant modifications in the organization of psychological and psychotherapeutic support even during the first weeks of the COVID-19 outbreak in Ukraine. The first responses of practitioners were related to (a) their experience and type of affiliation, (b) the main approach, (c) the subjective readiness or non-readiness to modify the usual form of work, (d) the way of interpreting the patient’s anxieties, (e) the lethal cases of coronavirus in the area of living.